2020
DOI: 10.1111/jmwh.13094
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women with Obesity Have Unique Perceptions About Gestational Weight Gain, Exercise, and Support for Behavior Change

Abstract: Introduction Prepregnancy obesity and excessive gestational weight gain (GWG) pose health risks to woman and fetus, yet gestational weight management interventions are largely unsuccessful. Little research examines the perceptions of women with obesity about weight gain and exercise. Although women with obesity have different body habitus and life experiences, most studies combine overweight and obese women into one group. Methods We conducted 3 focus groups with pregnant women with obesity to determine percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 40 publications
5
55
0
Order By: Relevance
“…Our results are in line with recent ndings, notably the intervention effect in prenatal care and goal setting as favorable to physical activity behaviors in overweight women [23,24]. A signi cant difference in sedentary physical activity was observed in the pre-pregnancy overweight women.…”
Section: Counseling and Pa Behaviorssupporting
confidence: 92%
“…Our results are in line with recent ndings, notably the intervention effect in prenatal care and goal setting as favorable to physical activity behaviors in overweight women [23,24]. A signi cant difference in sedentary physical activity was observed in the pre-pregnancy overweight women.…”
Section: Counseling and Pa Behaviorssupporting
confidence: 92%
“…This con ict could be due to overly general counseling or having too many issues to discuss during antenatal visits. Previous qualitative interview studies reported inconsistent advice on weight management and knowledge gaps in diet or exercise recommendations during pregnancy, similar to our ndings [12,28]. A lack of skills needed to cook healthy meals and follow a healthy lifestyle was also identi ed.…”
Section: Discussionsupporting
confidence: 82%
“…Some of the women had negative experiences during previous health care encounters due to their being overweight. Previous studies also reported similar ndings; discussing weight during antenatal visits can be stigmatizing and can make women less receptive to advice or support [27,28]. These experiences might inhibit women from accepting any attempts to intervene in their weight situation or provide weight management support.…”
Section: Discussionmentioning
confidence: 71%
“…Some of the women spoke about negative experiences during previous health care encounters due to their being overweight. Previous studies have also reported similar findings; discussing weight during antenatal visits can be stigmatizing and can make women less receptive to advice or support [ 12 , 28 ]. These experiences might inhibit women from accepting any attempts to intervene in their weight situation or provide weight management support.…”
Section: Discussionsupporting
confidence: 65%